The Effects of Instructional Strategies, College Division, and Gender on Students’ Performance in College Algebra at a University in South Texas - Oviedo, Andres Padilla; Mundy, Marie Anne; Kupczynski, Lori (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2016)
College Algebra courses have often served as gatekeepers to advancement toward a bachelor’s degree for many undergraduate students in colleges and universities all over the United States. As College Algebra is a core requirement for graduation, it is very important that fail and drop rates for this course be minimized. The ability to pass this class has a direct influence on 4-year/6-year graduation rates as well as retention rates for undergraduate students. Research has been carried out throughout the United States in attempts to tackle this issue. The present study was designed to explore the differences in final grades in College Algebra courses regarding different instructional strategies, college division and gender. Test findings indicated that the performance of college students as measured by final grade in College Algebra courses was significantly different among diverse instructional strategies. In addition, the performance of college students as measured by final grade in College Algebra courses was not significantly different in each college division or gender for different instructional strategies. Findings provided useful information for increasing student retention in college mathematics courses. Students will be more likely to learn and retain mathematical knowledge when diverse approaches for teaching and learning mathematics are applied.